Exploring the associations between ankle dorsal and plantar flexion strength, reactive strength index, and balance in elite youth soccer players - Kayhan, R. F.; Terzi, E.; Bayrakdaroglu, S.; Ceylan, H. I.; Morgans, R.; Nikolaidis, P. T. (Sport Sciences for Health, 2024)
Background Enhanced muscular strength has been widely acknowledged as a fundamental determinant of improved performance in the lower extremities. However, the specific impact of ankle strength on explosive strength and balance remains inadequately elucidated. Consequently, this study aims to (a) evaluate balance, reactive power, and flexor-extensor muscle balances in soccer players, and (b) evaluate ankle dorsal and plantar flexion muscle strength as predictive factors for reactive strength index and balance performance.